(untitled) (Teología, 2020)
At the beginning of the Academic year of 2010, the author gave this lecture on “Theology in the context of epochal change”. This epochal shift challenges theology in its role of interpretation and discernment and its suitability to process meaning and introduce the symbolic dimension as a new paradigm. In this context, the author proposed interdisciplinarity in the Faculty of Theology and the University as a means of thinking on one’s own faith in relation to the others.